Halogen‐ and Hydrogen‐Bonded Salts and Co‐crystals Formed from 4‐Halo‐2, 3, 5, 6‐tetrafluorophenol and Cyclic Secondary and Tertiary Amines: Orthogonal and Non‐orthogonal Halogen and Hydrogen Bonding, and Synthetic Analogues of Halogen‐Bonded Biological Systems. Issue 22 (5th May 2014) - Takemura, Akihiro; McAllister, Linda J.; Hart, Sam; Pridmore, Natalie E.; Karadakov, Peter B.; Whitwood, Adrian C.; Bruce, Duncan W.
Abstract Co‐crystallisation of, in particular, 4‐iodotetrafluorophenol with a series of secondary and tertiary cyclic amines results in deprotonation of the phenol and formation of the corresponding ammonium phenate. Careful examination of the X‐ray single‐crystal structures shows that the phenate anion develops a CO double bond and that the CC bond lengths in the ring suggest a Meissenheimer‐like delocalisation. This delocalisation is supported by the geometry of the phenate anion optimised at the MP2(Full) level of theory within the aug‐cc‐pVDZ basis (aug‐cc‐pVDZ‐PP on I) and by natural bond orbital (NBO) analyses. With sp2 hybridisation at the phenate oxygen atom, there is strong preference for the formation of two non‐covalent interactions with the oxygen sp2 lone pairs and, in the case of secondary amines, this occurs through hydrogen bonding to the ammonium hydrogen atoms. However, where tertiary amines are concerned, there are insufficient hydrogen atoms available and so an electrophilic iodine atom from a neighbouring 4‐iodotetrafluorophenate group forms an I⋅⋅⋅O halogen bond to give the second interaction. However, in some co‐crystals with secondary amines, it is also found that in addition to the two hydrogen bonds forming with the phenate oxygen sp2 lone pairs, there is an additional intermolecular I⋅⋅⋅O halogen bond in which the electrophilic iodine atom interacts with the CO π‐system. All attempts to reproduce this behaviour with 4‐bromotetrafluorophenol were unsuccessful. These structural motifs are significant as they reproduce extremely well, in low‐molar‐mass synthetic systems, motifs found by Ho and co‐workers when examining halogen‐bonding interactions in biological systems. The analogy is cemented through the structures of co‐crystals of 1, 4‐diiodotetrafluorobenzene with acetamide and with N‐methylbenzamide, which, as designed models, demonstrate the orthogonality of hydrogen and halogen bonding proposed in Ho's biological study.